The Parental Pressure and the Impacts to the Main Characters in 3 Idiots - Nuansa Citra Herdindha; Theophilus J Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2014)
This thesis deals with the parental pressure and how it gives impacts toward children in 3 Idiots. This thesis uses the parental pressure concept by Medora M. Sletten and anxiety theory by Sigmund Freud. The aim of this study is to reveal that Farhan and Raju get two kinds of parental pressure, they are direct and indirect pressures. Later on, the impact of the pressure makes both characters experience anxiety, they are, reality anxiety and neurotic anxiety. Through this analysis, it can be concluded that Farhan and Raju get the pressure from their parents, and since both the main characters suppress their own ego, they suffer anxiety